2012
DOI: 10.1155/2012/109705
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transmission ofPlasmodium falciparumin a Highly Malaria Endemic Area of Burkina Faso

Abstract: Malaria congenital infection constitutes a major risk in malaria endemic areas. In this study, we report the prevalence of transplacental malaria in Burkina Faso. In labour and delivery units, thick and thin blood films were made from maternal, placental, and umbilical cord blood to determine malaria infection. A total of 1,309 mother/baby pairs were recruited. Eighteen cord blood samples (1.4%) contained malaria parasites (Plasmodium falciparum). Out of the 369 (28.2%) women with peripheral positive parasitem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
10
27
5
Order By: Relevance
“…This shows that the prevalence of infection at delivery has been relatively stable over the years despite the implementation of the IPT p policy in Cameroon. The prevalence of placental malaria parasite infection was lower than that of peripheral malaria parasite infection, which is consistent with some previous observations [17], [24]. It is however contrary to the trends reported by Achidi et al [12], Anchang-Kimbi et al [10] and Leke et al [11] who found prevalence of placental malaria parasite infection higher than that of peripheral malaria parasite infection, as commonly admitted [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This shows that the prevalence of infection at delivery has been relatively stable over the years despite the implementation of the IPT p policy in Cameroon. The prevalence of placental malaria parasite infection was lower than that of peripheral malaria parasite infection, which is consistent with some previous observations [17], [24]. It is however contrary to the trends reported by Achidi et al [12], Anchang-Kimbi et al [10] and Leke et al [11] who found prevalence of placental malaria parasite infection higher than that of peripheral malaria parasite infection, as commonly admitted [25].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of neonatal malaria parasite infection (6.0%) was lower than the prevalence reported in the South West [12], [30] and Centre Regions of Cameroon [31], but higher than that found by Anchang-Kimbi [32] in Cameroon and Ouédraogo et al [24] in Burkina Faso. A similar value was found in Tanzania [33] and North Central Nigeria [17].…”
Section: Discussioncontrasting
confidence: 61%
“…The prevalence found in this study is similar to the low prevalence of 1.4 % reported in Burkina Faso [9] or 2.2 % reported in Ghana [8], but lower than the numbers reported from studies in Nigeria [6, 17–20]. However comparisons between studies are difficult to make due to the different methodologies being used (type of sample or type of diagnostic test), the different study populations being observed (symptomatic versus asymptomatic newborns) or the different contextual levels of malaria endemicity.…”
Section: Discussionsupporting
confidence: 89%
“…In Accra, Ghana newborns presented with ≤50 parasites/µL [8] and in Burkina Faso, the mean parasite density among newborns was 316 parasites/µL [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Congenital malaria due to P. falciparum is reportedly rare in hyperendemic areas, where pregnant woman can pass on antibodies against the parasite to their newborn babies. Thus, even though maternal asymptomatic malaria is common, congenital malaria is not [8][9][10][11]. However, recent reports suggest that congenital P. falciparum malaria is not as rare as previously believed [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%